Nitric-Oxide Supplementation for Treatment of Long-Term Complications in Argininosuccinic Aciduria - Nagamani, Sandesh C.S. (Elsevier, 2012)
Argininosuccinate lyase (ASL) is required for the synthesis and channeling of L-arginine to nitric oxide synthase (NOS) for nitric oxide (NO) production. Congenital ASL deficiency causes argininosuccinic aciduria (ASA), the second most common urea-cycle disorder, and leads to deficiency of both ureagenesis and NO production. Subjects with ASA have been reported to develop long-term complications such as hypertension and neurocognitive deficits despite early initiation of therapy and the absence of documented hyperammonemia. In order to distinguish the relative contributions of the hepatic urea-cycle defect from those of the NO deficiency to the phenotype, we performed liver-directed gene therapy in a mouse model of ASA. Whereas the gene therapy corrected the ureagenesis defect, the systemic hypertension in mice could be corrected by treatment with an exogenous NO source. In an ASA subject with severe hypertension refractory to antihypertensive medications, monotherapy with NO supplements resulted in the long-term control of hypertension and a decrease in cardiac hypertrophy. In addition, the NO therapy was associated with an improvement in some neuropsychological parameters pertaining to verbal memory and nonverbal problem solving. Our data show that ASA, in addition to being a classical urea-cycle disorder, is also a model of congenital human NO deficiency and that ASA subjects could potentially benefit from NO supplementation. Hence, NO supplementation should be investigated for the long-term treatment of this condition.